PRESTRESSED CONCRETE I-GIRDER BRIDGE DESIGN FOR TERMINAL PETIKEMAS SURABAYA ÃâÃâ KALIMAS RAILWAY - AKHYAR FAISAL, FADLAN
Port of Tanjung Perak and Port of Teluk Lamong accommodate the shipping of goods through water transport in East Java. However, trailer trucks only provide landside transportation at the time. As demand of trips increases, an alternative to the current road-based transportation mode is essential to further tackle the challenge in order to reduce the congestion on road network around the ports. An elevated railroad for freight trains is generating considerable interest in terms of solving the problem. Therefore, an elevated railroad design that connects the two ports along with train operation plan and feasibility study are carried out in this publication. In this task will be designed a fly rail designed by using prestressed concrete with cross section of I-Girder. The bridge is planned to have two rail lines with a rail width of 1067 mm. Prestress bridges are currently favored in the construction world because with the same cross-section, prestressed concrete can bear a larger load. The prestressed I-Girder bridge is used because it is relatively more efficient in construction. The bridge uses a 1067 mm rail width as it is commonly used in Indonesia. The I-Girder cross-section determination is used based on the load to be borne. It is planned that there will be three spans, namely 45 m, 30 m, and 20 m. Each span will have different load and cross section characters. In addition to reviewing the load and cross-sectional capacity, prestressed concrete should also be reviewed for the cross-sectional stresses that occur. Stress must be checked at initial conditions, construction stage, and final conditions. For precast concrete, no tensile stress is permitted. Based on design, for spans 45 m and 30 m using H-210 girder, while for span 20 m using H-160 girder For a span of 45 m requires 5 tendons with each tendon containing 19 starnd. For a span of 30 m requires 3 tendons with each tendon containing 19 starnd. For a span of 20 m requires 2 tendons with each tendon containing 19 strands.